Phase 3, Multicenter Open‐Label study to investigate the efficacy of elbasvir and grazoprevir fixed‐dose combination for 8 weeks in treatment‐naïve, HCV GT1b‐infected patients, with non‐severe fibrosis. (1st June 2020) - Abergel, Armand; Asselah, Tarik; Mallat, Arianne; Chanteranne, Brigitte; Faure, Frederic; Larrey, Dominique; Gournay, Jerome; Loustaud‐Ratti, Veronique; Di Martino, Vincent; Fouchard‐Hubert, Isabelle; Pol, Stanislas; Bailly, Francois; et al.
Abstract: Background: Genotype 1b is the most common HCV genotype worldwide, accounting for the largest proportion of infections in Europe, Russia, Latin America and Asia. Reducing treatment duration can improve adherence, reduce drug exposure and cost. Accordingly, we evaluated the efficacy of 8 weeks fixed‐dose combination of grazoprevir‐elbasvir in treatment‐naïve patients, with non‐severe fibrosis. Methods: HCV mono‐infected and treatment naïve patients with non‐severe fibrosis (Fibroscan ® <9.5 kPa and Fibrotest ® < 0.59) were enrolled in a study which included 117 patients. Genotyping by sequencing identified five patients with non‐1b genotype (two GT1a, one GT1h, one GT1e and one GT1l). Thus, we included in the final analysis 112 GT1b patients. The primary end point was the proportion of patients with HCVRNA below the lower limit of quantification 12 weeks after treatment (SVR12). Findings: Mean age was 54 ± 13 years, 31% were men and viral load was higher than 800.000 IU/mL in 70 of 112 patients (63%). Using Fibroscan ®, 100 had F0‐1 fibrosis score. FIB‐4 lower than 1.45 and APRI less than 1 was found in 74/112 (66%) and 107/112 (95%) patients respectively. Relapse occurred in three patients by week 12. These three patients had a viral load higher than 6 million IU/mL and NS5A Y93H RAS (resistance‐associated substitution). Then, modified intention‐to‐treat SVR12 for patients with genotype 1b was 109/112 (97%). By week 24; five relapses were observed and all had the Y93H RAS at relapse. SVR12 was achieved in 100% of patients with a baseline viral load below 6 million and decreased to 98% (98/100) by follow‐up week 24. Interpretation: Naïve patients with genotype 1b and non‐severe fibrosis can achieve an SVR12 of 97% and an SVR24 of 95%. Then, these patients can be treated with grazoprevir‐elbasvir for 8 weeks.